The influential role of artificial intelligence (AI) adoption in digital value creation for small and medium enterprises (SMEs): does technological orientation mediate this relationship? - Muhammad Farhan, Jalil; Patrick, Lynch; Dayang Affizzah, Awang Marikan; Abu Hassan, Md Isa (Springer Nature, 2024)
Despite the increasing consensus on the disruptive potential of artificial intelligence (AI) and its positive impact on value creation for Small and Medium Enterprises (SMEs), there is a notable absence of empirical evidence in the academic literature addressing this correlation. Therefore, primary objective of this study is to identify the significant relationship between the intention to adopt AI and the digital value creation of SMEs. Additionally, this study determines the mediating role of technology orientation in the relationship between AI adoption and digital value creation. Data were collected from 335 Malaysian SMEs owners/managers who filled out self-administered/online questionnaires. The data were analyzed and hypotheses were tested using structural equation modeling (AMOS 21.0). Mediating effects were determined by bootstrapping confidence intervals. The findings of the study demonstrate that the adoption of AI interacts to encourage SMEs to enhance their digital value creation. Furthermore, AI and digital value creation were complementary mediated by technology orientation. The study makes significant contributions to theoretical advancements in research on the SME sector and the theoretical progress of AI, particularly within the context of digital SMEs. The practical value of the framework is closely tied to its applications for researchers, SME owners/managers, and aspiring entrepreneurs seeking to harness the potential of AI in an entrepreneurial setting.